login
a(n-1)+k=a(n) => a(n)*k=a(n+1).
1

%I #4 Sep 05 2017 17:11:10

%S 1,3,6,18,216,42768,1819863936,3311826913612597248,

%T 10968197499701667312529793029329125376,

%U 120301356392461906290006219878693096559247086148184247242087281541542576128

%N a(n-1)+k=a(n) => a(n)*k=a(n+1).

%C For +k and ^k see A057269. (Using *k and ^k gives another formulation of A014222. In this case the sequence could start 1,2 - see A014221.)

%t nxt[{a_,b_}]:={b,b(b-a)}; NestList[nxt,{1,3},9][[All,1]] (* _Harvey P. Dale_, Sep 05 2017 *)

%Y Cf. A057269.

%K easy,nonn

%O 0,2

%A _Jonas Wallgren_, Aug 22 2000

%E More terms from _Harvey P. Dale_, Sep 05 2017